Synthesis, Characterization, and Testing of PEG-PDMAEMA Diblock Smart Polymers - Laskowski, Elizabeth; Stubbs, Elizabeth; King, Brandon (My University, 2015)
In order to determine if PEG-PDMAEMA serves as both a polymer and a surfactant in EOR, testing of how viscosity and interfacial tension change of the aqueous PEG-PDMAEMA solution is needed. This can predict its ability to mix with oil.
Color poster with text, graphs, tables, and images.
Keywords: PEG-PDMAEMA; Chemistry; Smart polymers; Posters